Masculinity and transfemininity: Evidence in the film "Memories of My Body" - Wicaksono, Andri; Hastuti, Hastuti (LITERA, 2023)
As a distinct field of research, so-called transfemininity studies can be used for the purposes of creating strategic coalitions and exploring specificities and differences. This study aims to explore the life journey of Arjuna (Juno), a man who is also a trans feminist, through the perspective of masculinity studies. The sub focuses of this research include: 1) transfemininity, physical transformation 2) and socio-psychological transformation. This research is interpretive qualitative research that verbally narrates data in the film Memories of My Body which was broadcast in 2019 as the data source. The results of the study show that Juno as the main character is caught between past trauma, his profession as a Lengger dancer, his sexual orientation and being liked by other men. Not yet finished making peace with himself, the people around him also add to the chaos with the end of his return to the beginning, trans-feminity – masculinity. Gender and sex as the other side of the coin are simple constructs, so future studies should be carried out to provide additional insights into the gender identities that have been internalized, reproduced, and possibly opposed by 'women' in everyday life in the social environment.